2017
DOI: 10.1038/s41598-017-09399-4
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional quorum-quenching and antibiotic-acylase MacQ forms a 170-kDa capsule-shaped molecule containing spacer polypeptides

Abstract: Understanding the molecular mechanisms of bacterial antibiotic resistance will help prepare against further emergence of multi-drug resistant strains. MacQ is an enzyme responsible for the multi-drug resistance of Acidovorax sp. strain MR-S7. MacQ has acylase activity against both N-acylhomoserine lactones (AHLs), a class of signalling compounds involved in quorum sensing, and β-lactam antibiotics. Thus, MacQ is crucial as a quencher of quorum sensing as well as in conferring antibiotic resistance in Acidovora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…Besides, our group and other two research groups reported that AHL-acylases (MacQ, AhlM, and KcPGA) could function as β-lactam acylase, and indeed degrade PENG via hydrolysis of the amide bond ( Park et al, 2005 ; Mukherji et al, 2014 ; Kusada et al, 2017 ). Furthermore, we recently solved the X-ray crystal structure of MacQ, and found that the degradation products of C 10 -HSL and PENG by MacQ were commonly accommodated in the same hydrophobic active-site pocket, indicating that both compounds were hydrolyzed by MacQ in the same degradation mechanism ( Yasutake et al, 2017 ). Perhaps, some AHL-acylases (β-lactam acylases) may have broad substrate specificity that appears to be structurally indistinguishable from both AHL-signals and β-lactam antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, our group and other two research groups reported that AHL-acylases (MacQ, AhlM, and KcPGA) could function as β-lactam acylase, and indeed degrade PENG via hydrolysis of the amide bond ( Park et al, 2005 ; Mukherji et al, 2014 ; Kusada et al, 2017 ). Furthermore, we recently solved the X-ray crystal structure of MacQ, and found that the degradation products of C 10 -HSL and PENG by MacQ were commonly accommodated in the same hydrophobic active-site pocket, indicating that both compounds were hydrolyzed by MacQ in the same degradation mechanism ( Yasutake et al, 2017 ). Perhaps, some AHL-acylases (β-lactam acylases) may have broad substrate specificity that appears to be structurally indistinguishable from both AHL-signals and β-lactam antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The model protein of subfamily 5C9IA is the aforementioned MacQ, an AHL acylase from Acidovorax sp. MR-S7, active towards both AHLs and β-lactam antibiotics [47]. In addition, a phylogenetic study was performed using MEGA X based on the amino acid sequences of 31 Ntn-hydrolases with reported amidase activities (Figure 4).…”
Section: Phylogenetic Analysis Of Slpa and Auaac Acylasesmentioning
confidence: 99%
“…Within this framework, it is notably, that the recently uncovered acylase MacQ has been described to be involved in QQ and antibiotic resistance. Thereby, MacQ acts against AHLs and Penicillin G and is an acylase belonging to the Ntn family 21 .…”
Section: Resultsmentioning
confidence: 99%